Research and the practitioner : dissemination of research results within the library-information profession - Lynam, Peter; Slater, Margaret; Walker, Rennie (London : Aslib, 1982)
This book deals with the dissemination of research result within the library information profession.
oo 11/04/2019
Loans
Keywords: Library science; Information science; Library science literature; Information science literature; Library education (Continuing education); Readership surveys; Communication in library science; Communication in information science